Delay-Aware Power Control for D2D Communication With Successive Interference Cancellation and Hybrid Energy Source - Li, Jiandong; Huang, Sheng (IEEE wireless communications letters, 2017)
We investigate joint flow control, successive interference cancellation (SIC) scheduling, and power control design for delay-aware device-to-device communication in a multi-cell network with hybrid energy source. Aiming to maximize the time-average total throughput of network, we propose a flow control scheme and a two-stage SIC-based power control strategy based on perturbed Lyapunov optimization and sequential convex programming, subject to the SIC feasibility, queueing stability, finite energy storage, and energy balance. Simulation results exhibit the superiority of our proposed strategy against alternative strategies.